Quick Respond Indonesian Standart (QRIS) dalam Ber-Transaksi Secara Go Digital di UMKM Keripik Pisang UD. Muser Desa Pandanagung Kecamatan Soko Kabupaten Tuban - Irawan, Agus Wahyu; Fitri, Nur Lailatul; Maeni, Popy Nur (Universitas Islam Lamongan, 2023)
In 2019, the banana chips business utilizing QRIS payment was solely owned by UD. Muser. On average, 77 customers per month engaged in transactions using QRIS, with fluctuations in numbers. The production facility is located 25 minutes away from Bojonegoro and 53 minutes from Tuban, far from major cities. The customers of Banana Chips UD Muser are sales representatives who personally pick up the products from the production site. Banana Chips UD Muser has successfully entered Minimarts around Parengan, Soko, and Bojonegoro. The embedded strategy model employed a mixed method design, utilizing both primary methods (quantitative or qualitative) and secondary methods (qualitative or quantitative) simultaneously. By combining both types of data, a comprehensive analysis was obtained. Based on the SPSS Coefficients output, the significance value (Sig) of the QRIS variable (X) is 0.000, where 0.000 < 0.05. Therefore, the hypothesis is accepted, indicating that QRIS is effective in public payment transactions. The t-test results show a t-value of 8.082 for the QRIS variable. Since the calculated t-value (8.082) is greater than the table t-value (2.005), it can be concluded that the hypothesis is accepted. QRIS is effective in digital payment transactions at UD. Muser. The effectiveness of QRIS usage is evident from the widespread adoption by buyers. Customers are satisfied with the QRIS method as it facilitates seamless digital transactions. Buyers find QRIS easy to use, requiring only a barcode scan specifying the purchase amount, making the transaction process straightforward and convenient.